THE ROLE OF CONTINUOUS EDUCATION SYSTEM IN IMPROVING PERSONAL ECOLOGICAL CULTURE - Abdumalikov Abdulatif Abidjanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The social significance of the development of ecological culture in the system of relations between man and nature is studied in this article. Also, the priority tasks of the formation of environmentally conscious activities based on the promotion of environmental culture were analyzed.